Impaired NLRP3 inflammasome activity during fetal development regulates IL‐1β production in human monocytes. Issue 1 (17th November 2014) - Sharma, Ashish A.; Jen, Roger; Kan, Bernard; Sharma, Abhinav; Marchant, Elizabeth; Tang, Anthony; Gadawski, Izabelle; Senger, Christof; Skoll, Amanda; Turvey, Stuart E.; Sly, Laura M.; Côté, Hélène C.F.; et al.
<x xml:space="preserve">Abstract</x> Interleukin‐1β (IL‐1β) production is impaired in cord blood monocytes. However, the mechanism underlying this developmental attenuation remains unclear. Here, we analyzed the extent of variability within the Toll‐like receptor (TLR)/NLRP3 inflammasome pathways in human neonates. We show that immature low CD14 expressing/CD16pos monocytes predominate before 33 weeks of gestation, and that these cells lack production of the pro‐IL‐1β precursor protein upon LPS stimulation. In contrast, high levels of pro‐IL‐1β are produced within high CD14 expressing monocytes, although these cells are unable to secrete mature IL‐1β. The lack of secreted IL‐1β in these monocytes parallels a reduction of NLRP3 induction following TLR stimulation resulting in a lack of caspase‐1 activity before 29 weeks of gestation, whereas expression of the apoptosis‐associated speck‐like protein containing a CARD and function of the P2×7 receptor are preserved. Our analyses also reveal a strong inhibitory effect of placental infection on LPS/ATP‐induced caspase‐1 activity in cord blood monocytes. Lastly, secretion of IL‐1β in preterm neonates is restored to adult levels during the neonatal period, indicating rapid maturation of these responses after birth. Collectively, our data highlight important developmental mechanisms regulating IL‐1β responses early in gestation, in part due to a downregulation of TLR‐mediated NLRP3 expression. Such mechanisms may serve to limit potentially damaging inflammatory responses in a developing fetus.